Epigrafi, armi, trofei. Il palazzo del cardinale Bonifacio Bevilacqua a Ferrara (1601) - Mattei, Francesca (Opus Incertum, 2022)
The essay focuses on the ‘talking’ façade of Palazzo Bevilacqua in Ferrara, lavishly decorated by trophies, panoplies, and eight mottos in Latin. The text is divided into three parts. The first is dedicated to the analysis of the palace, with particular attention to the iconographic programme sculpted on the façade, refashioned by the cardinal Bonifacio Bevilacqua in 1601. The second focuses on the interpretation of the epigraphs in relation to the antiquarian culture of the city. The third proposes the reconstruction of the cultural biography of the patron of the building. Through the analysis of published and unpublished documents and sources, the essay proposes the first in-depth investigation of Palazzo Bevilacqua, in order to place it in the artistic and cultural context of Ferrara, where the new political establishment – a few years after the Devolution to the Papal State (1598) – coexisted with the cultural legacy forged by the duke Alfonso II d’Este (1559-1597) and his entourage of antiquarians Enea Vico, Agostino Mosti and Pirro Ligorio.